THE APPLICATION OF AUTHENTIC ASSESSMENT WITH FEEDBACK TO IMPROVE THE COMPETENCE OF MTS 2 BANDUNG STUDENTS IN CONSTRUCTING A SCIENTIFIC REPORT OF MOTION MATERIAL IN SCIENCE LEARNING - Nuryantini, A. Y.; Setiadi, T.; Kurniawan, K.; Farida, I. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2015)
This research was carried out to describe the application of authentic assessment with feedback in science learning of motion material which can increase the grade VIII G MTs Negeri 2 Kota Bandung students’ ability of making scientific reports and to analyse the increase. This classroom action research was performed at Madrasah Tsanawiyah Negeri 2 Kota Bandung in the even semester 2014/2015 academic year with 35 students consisting of 18 boys and 17 girls as the subjects. The success indicator of the research was a minimum of 80% of the students were able to make scientific reports in good category (with minimum score of 80). The result showed that the application of the authentic assessment with the feedback increased the ability of students of MTs Negeri 2 Kota Bandung in writing the scientific reports. There was an increase of students’ ability in writing the scientific reports from the first cycle to the second one. Initially, 14% of the students got good category in the first cycle. This number increased, then, to 83% in the second cycle. Penelitian ini dilakukan untuk mendeskripsikan penerapan penilaian otentik dengan feedback dalam pembelajaran IPA materi gerak yang dapat meningkatkan kemampuan menulis laporan ilmiah dan menganalisis peningkatan kemampuan menulis laporan ilmiah siswa kelas VIII G MTs Negeri 2 Kota Bandung. Penelitian yang dilakukan merupakan penelitian tindakan kelas. Subjek penelitian adalah 35 orang siswa kelas VIII G yang terdiri dari 18 laki-laki dan 17 perempuan. Tempat penelitian dilaksanakan di Madrasah Tsanawiyah Negeri 2 Kota Bandung pada semester genap tahun pelajaran 2014/2015. Indikator keberhasilan dari penelitian tindakan kelas yang dilakukan adalah minimal 80% dari siswa memiliki kemampuan menulis laporan ilmiah dalam kategori baik (dengan skor minimal 80). Hasil penelitian menunjukkan bahwa kami telah berhasil menerapkan penilaian otentik dengan feedback yang dilakukan guru dalam pembelajaran IPA materi gerak untuk meningkatkan kemampuan siswa MTsN 2 Bandung dalam menyusun laporan ilmiah. Kemampuan menulis laporan ilmiah siswa mengalami peningkatan siklus I ke siklus II yang semula sebesar 14 % menjadi 83 % jumlah siswa yang berkategori baik.